Subcellular compartmentalization of aluminum reduced its hazardous impact on rye photosynthesis. (15th December 2022) - de Sousa, Alexandra; AbdElgawad, Hamada; Fidalgo, Fernanda; Teixeira, Jorge; Matos, Manuela; Tamagnini, Paula; Fernandes, Rui; Figueiredo, Francisco; Azenha, Manuel; Teles, Luís Oliva; Korany, Shereen Magdy; Alsherif, Emad A.; et al.
Abstract: Aluminum (Al) toxicity limits crops growth and production in acidic soils. Compared to roots, less is known about the toxic effects of Al in leaves. Al subcellular compartmentalization is also largely unknown. Using rye ( Secale cereale L.) Beira (more tolerant) and RioDeva (more sensitive to Al) genotypes, we evaluated the patterns of Al accumulation in leaf cell organelles and the photosynthetic and metabolic changes to cope with Al toxicity. The tolerant genotype accumulated less Al in all organelles, except the vacuoles. This suggests that Al compartmentalization plays a role in Al tolerance of Beira genotype. PSII efficiency, stomatal conductance, pigment biosynthesis, and photosynthesis metabolism were less affected in the tolerant genotype. In the Calvin cycle, carboxylation was compromised by Al exposure in the tolerant genotype. Other Calvin cycle-related enzymes, phoshoglycerate kinase (PGK), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), triose-phosphate isomerase (TPI), and fructose 1, 6-bisphosphatase (FBPase) activities decreased in the sensitive line after 48 h of Al exposure. Consequentially, carbohydrate and organic acid metabolism were affected in a genotype-specific manner, where sugar levels increased only in the tolerant genotype. In conclusion, Al transport to the leaf and compartmentalization in the vacuoles tolerant genotype's leaf cells provide complementary mechanisms of Al tolerance, protecting the photosynthetic apparatus and thereby sustaining growth. Graphical abstract: Image 1 Highlights: Al within cell leaves is mobilized to organelles in a genotype specific manner. Differential Al compartmentalization in vacuoles is a key to enhanced Al tolerance in rye. Photosynthetic apparatus was more compromised in the sensitive genotype. Al inhibited pigment biosynthesis and photosynthesis metabolism in a genotypic-specific manner.